KARAKTERISTIK LELAKI SEKS DENGAN LELAKI (LSL) DI WILAYAH KERJA PUSKESMAS X DI KABUPATEN DEMAK - Yuwanti (Jurnal Profesi Bidan Indonesia, 2023)
Background: Globally the number of men having sex with men (MSM) is estimated to account for 3% of the total population. MSM is a phenonema of personal, emotional and sexual attraction to the same sex. This behavior is at risk of increasing various sexually transmitted diseases and HIV AIDS.Objective: This study aims to determine the characteristics of Men Sex with Men (MSM) in the working area of Puskesmas X in Demak Regency.Method: This type of research is survey research. The study sample was 21 people by accidental sampling.Results: the study showed that the age of most respondents was reproductive age aged < 18-> 35 years, respondents who had a high school education (66.7%), VCT results of all respondents were negative (100%), most respondents had never used condoms (42.(%), 47.6% had multipartner partners and all respondents (100%) had no history of STIs.Conclusion: that the characteristics of MSM in the working area of puskesmas X in Demak Regency consist of age, education level, VCT test results, condom use, sexual partners, and STI history